Cyberbullying impacts on users’ satisfaction with information and communication technologies: the role of Perceived Cyberbullying Severity - Camacho Ahumada, Sonia (My University, 2015)
Cyberbullying is a term that encompasses aggressive behaviours performed through different information and communication technologies (ICT), with the intention to harm or cause discomfort to others. Cyberbullying has gained prominence due to reported cases of teenage suicides linked to cyberbullying. Researchers have studied the prevalence and outcomes of cyberbullying (e.g. truancy) and strategies used by victims to deal with cyberbullying (e.g. email address change). However, researchers have not taken into account victims’ perceptions of the severity of the cyberbullying they experience and how those perceptions affect them at a personal level and their experience with ICT. This study combines Transactional Theory of Stress and Coping with the Expectation-Confirmation Theory and proposes two research models that will aid in understanding (i) the contextual factors that affect victims’ perceptions of cyberbullying, and (ii) the consequences of those perceptions on victims’ satisfaction with the ICT through which cyberbullying occurs. In addition, this study proposes two secondary objectives aimed at (i) developing and validating a scale to measure victims’ perception of cyberbullying severity and (ii) exploring its impact on victims’ use of different coping mechanisms. A survey-based study involving 229 cyberbullying victims is employed to empirically validate the proposed theoretical models, using structural equation modeling techniques. Results indicate that victims’ perception of the severity of a cyberbullying episode affects her/him at a personal level and negatively impacts her/his ICT beliefs, which in turn, impact her/his satisfaction with ICT. The analysis of different contextual factors indicates that the harshness of the message(s) the victim receives, the importance of the ICT through which cyberbullying occurred to her/him, her/his self-esteem, and knowing who the bully is affect a victim’s evaluation of the severity of a cyberbullying episode. Implications of these results for academics and practitioners, as well as limitations of this study, are discussed.
Keywords: cyberbullying; satisfaction; technology; severity